Veni, vidi, scripsi : écrire l'histoire dans l'Antiquité - Duchêne, Pauline; Bellissime, Marion (PrimaLun@, 2021)
This volume collects together papers based on the fruitful exchanges that occurred during the first three years of the research seminar "Historiographies antiques" (Ancient Historiographies) - organized at the École normale supérieure of Paris and Lyon II University (France). It aims at giving access to French speaking readers to a better understanding of the way history was written in ancient times, from classical Athens to late-Antiquity scholiasts. Accordingly, following a consistent introduction by M. Bellissime and P. Duchêne, presenting the lastest research developments in this topic, ten contributions provide illustration cases that are, as ancient historians themselves, at a crossroad between history and literature. On the historical side, G. Van Heems explores the question of the sources and A. Jayat details the construction of a speech. In addition, F. Galtier, then O. Devillers focuse on the treatment of a major event, i.e. the death of an emperor. On the literary side, M. Simon, then I. Cogitore and L. Autin study the role of echoes in the global meaning of historical texts, respectively through references to religious matters and in speeches given by women. D. Barcat and A. Pulice both show how the whole structure of a work could be designed, whereas P. Ponchon and R. Cytermann analyze the elements defining the genre. By publishing together contributions by well-established leading researchers and new generations of scholars, this volume is also proof of the vitality and the interest of this research field in France.